Occurrence of antibiotic resistant C. jejuni and E. coli in wild birds, chickens, environment and humans from Orang Asli villages in Sungai Siput, Perak, Malaysia - Ibrahim Mohamed, Mohamed Yousif; Abu, Jalila; Abdul Aziz, Saleha; Zakaria, Zunita; Rashid, Abdul; Mohamed, Elmutaz Atta Awad (Science Publications, 2019)
JALILA BINTI ABU/// MOHAMED YOUSIF IBRAHIM MOHAMED,SALEHA BINTI ABDUL AZIZ,ZUNITA BINTI ZAKARIA/// Abdul Rashid,Elmutaz Atta Awad